Journey of Self-Discovery and Historical Pain reflected through Wiradjuri Culture in Tara June Winch’s The Yield - Donny Syofyan (Andalas International Journal of Socio-Humanities, 2023)
Discrimination and violence against indigenous communities have persisted for decades, with many individuals sacrificing their lives to preserve cultural values and languages. Tara June Winch, in her novel The Yield, artfully captures the love and honor for language, portraying the history of Wiradjuri culture and the indigenous people's enduring struggle for survival. The characters are meticulously crafted, allowing readers to grasp the context and empathize with their emotions. August, the central character, returns after decades for her grandfather's funeral, revealing the stagnation in the community's living conditions. As the narrative unfolds, August's memories, intertwined with her grandfather's dictionary, provide a poignant journey through time, shedding light on the harsh realities faced by the indigenous community. Winch masterfully weaves together elements of love, culture, and resilience, delivering a powerful narrative that resonates with the ongoing battle against discrimination and violence.